Trends in the Degree of Control and Treatment of Cardiovascular Risk Factors in People With Type 2 Diabetes in a Primary Care Setting in Catalonia During 2007–2018 - Mata-Cases, Manel; Vlacho, Bogdan; Real, Jordi; Puig-Treserra, Ramon; Bundó, Magdalena; Franch-Nadal, Josep; Mauricio, Didac (Frontiers in Endocrinology, 2022)
Objective: To assess the trends in cardiovascular risk factor control and drug therapy from 2007 to 2018 in subjects with type 2 diabetes mellitus (T2DM). Materials and Methods: Cross-sectional analysis using yearly clinical data and treatment obtained from the SIDIAP database. Patients aged ≥18 years with a diagnosis of T2DM seen in primary care in Catalonia, Spain. Results: The number of T2DM patients increased from 299,855 in 2007 to 394,266 in 2018. We also found an increasing prevalence of cardiovascular disease, heart failure, and chronic kidney disease (from 18.4 to 24.4%, from 4.5 to 7.3%, and from 20.2 to 31.3%, respectively). The achievement of glycemic targets (HbA1c<7%) scarcely changed (54.9% to 55.9%). Major improvements were seen in blood pressure (≤140/90 mmHg: from 55% to 71.8%), and in lipid control (low-density lipoprotein cholesterol <100 mg/dl: 33.4% to 48.4%), especially in people with established cardiovascular disease (48.8 to 69.7%). Simultaneous achievement of all three targets improved from 12.5% to 20.1% in the overall population and from 24.5% to 32.2% in those with cardiovascular disease but plateaued after 2013. There was an increase in the percentage of patients treated with any antidiabetic drug (70.1% to 81.0%), especially metformin (47.7% to 67.7%), and DPP4i (0 to 22.6%). The use of SGLT-2 and GLP-1ra increased over the years, but remained very low in 2018 (5.5% and 2.1% of subjects, respectively). There were also relevant increases in the use of statins (38.0% to 49.2%), renin-angiotensin system (RAS) drugs (52.5% to 57.2%), and beta-blockers (14.3% to 22.7%). Conclusions: During the 2007-2018 period, relevant improvements in blood pressure and lipid control occurred, especially in people with cardiovascular disease. Despite the increase in the use of antidiabetic and cardiovascular drugs, the proportion of patients in which the three objectives were simultaneously achieved is still insufficient and plateaued after 2013. The use of antidiabetic drugs with demonstrated cardio renal benefits (SGLT-2 and GLP-1ra) increased over the years, but their use remained quite low.